2015
DOI: 10.4068/cmj.2015.51.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Use of Aripiprazole Augmentation in the Treatment of Major Depressive Disorder: From Clinical Trials to Clinical Practice

Abstract: Major depressive disorder (MDD) is a recurrent, chronic, and devastating disorder leading to serious impairment in functional capacity as well as increasing public health care costs. In the previous decade, switching therapy and dose adjustment of ongoing antidepressants was the most frequently chosen subsequent treatment option for MDD. However, such recommendations were not based on firmly proven efficacy data from well-designed, placebo-controlled, randomized clinical trials (RCTs) but on practical grounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…Along with multiple symptoms, this disorder is associated with recurrent thoughts of death or suicide 1,2. The prevalence of MDD differs among countries; the estimated lifetime prevalence of major depressive episodes was 1.5% in Taiwan, 7% in Korea, 19.0% in Lebanon, 9.2% in Germany, and 9.0% in Chile 3. The global prevalence of major depressive disorder is generally estimated to be between 3% and 6% 4.…”
Section: Introductionmentioning
confidence: 99%
“…Along with multiple symptoms, this disorder is associated with recurrent thoughts of death or suicide 1,2. The prevalence of MDD differs among countries; the estimated lifetime prevalence of major depressive episodes was 1.5% in Taiwan, 7% in Korea, 19.0% in Lebanon, 9.2% in Germany, and 9.0% in Chile 3. The global prevalence of major depressive disorder is generally estimated to be between 3% and 6% 4.…”
Section: Introductionmentioning
confidence: 99%
“…Since January 2013, two more RPCTs studying the efficacy of aripiprazole adjunctive use in the treatment of MDD were published. 26 The first study, The Aripiprazole Depression Multicenter Efficacy (ADMIRE) study, was designed to evaluate the efficacy and safety of aripiprazole augmentation in Japanese patients with MDD. 27 Subjects with an inadequate response to 8 weeks of ADT were randomized to receive placebo augmentation, fixed dose aripiprazole, or flexible dose aripiprazole for 6 weeks.…”
Section: The Current Market Statusmentioning
confidence: 99%
“…Table 4 Antidepressants and antipsychotics combinations with highest combined scores Among the nominated drug combinations, Aripiprazole is the only SGAs and is also the most recommended treatment options for AD+P. As a matter of fact, the combination of Aripiprazole and Sertraline has already been tested in clinical trials and showed superior efficacy in treating major depressive disorders (MDD) with no reports of safety concerns 54 . However, none of these drug pairs have been tested for AD+P in clinical trials.…”
Section: Systems Pharmacology Studies Provided Possible Explanations ...mentioning
confidence: 99%